The ADaptation and Anticipation Model (ADAM) of sensorimotor synchronization - Van Der Steen, Maria C.; Keller, Peter E. (Frontiers in Human Neuroscience, 2013)
A constantly changing environment requires precise yet flexible timing of movements. Sensorimotor synchronization (SMS) —the temporal coordination of an action with events in a predictable external rhythm— is a fundamental human skill that contributes to optimal sensory-motor control in daily life. A large body of research related to SMS has focused on adaptive error correction mechanisms that support the synchronization of periodic movements (e.g., finger taps) with events in regular pacing sequences. The results of recent studies additionally highlight the importance of anticipatory mechanisms that support temporal prediction in the context of SMS with sequences that contain tempo changes. To investigate the role of adaptation and anticipatory mechanisms in SMS we introduce ADAM: an ADaptation and Anticipation Model. ADAM combines reactive error correction processes (adaptation) with predictive temporal extrapolation processes (anticipation) inspired by the computational neuroscience concept of internal models. The combination of simulations and experimental manipulations based on ADAM creates a novel and promising approach for exploring adaptation and anticipation in SMS. The current paper describes the conceptual basis and architecture of ADAM.